Fomulasi PMT “Browntule” Brownis dengan Penambahan Tepung Tulang Ikan Lele terhadap Daya Terima dan Kandungan Calsium - Suprihartini, Cucuk; Puspita, Theresia (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2025)
Utilization of catfish bone flourl in food products consumed by the community can help intake the body's daily calcium needs. One way to utilize catfish bone flour into a food product that is widely liked is brownies. This type of research is quasi-experimental. The variables studied were the formulation of brownies with the addition of catfish bone flour and the acceptability of brownies as PMT for toddlers in Darungan Village, Pare District. The results of the study showed that the color acceptability of all the treatments above was in the good category, the highest value was 98.67% in the control and P1 treatment. The aroma acceptability of all the treatments above was in the good category, the highest value was 94.67 in the control and P2. The texture acceptability of all the treatments above was in the good category, the highest value was 85.33% in the P1 treatment. The taste acceptability of all the treatments above was in the good category, the highest value was 94.67% in the P2 treatment. Browntule 5%, meets the claim requirements as a calcium source product for toddlers. Browntule 10% meets the claim requirements as a calcium source product for the general public and pregnant women. The intake level of toddlers given 5% browntule PMT was 100%